Does domestic visitors' tourism expenditure intensify impoverishment in India?. (2022) - Nayak, Rasmita; Sahoo, Bimal Kishore; Mahalik, Mantu Kumar
Highlights: The welfare effect of households'' tourism spending in India is examined. The mid-aged people were dragged into poverty due to tourism spending. Hindus are more prone into poverty due to tourism spending compared to Muslims. There is higher percentage impoverishment of the rural population than the urban. Abstract: This study using the micro level data on households' tourism expenditure, examines the level of impoverishment in India caused by tourism spending. The result shows that the mid-aged people were dragged into poverty due to tourism spending. Hindus are more prone to poverty due to tourism spending compared to Muslims and other religious groups. There is higher percentage impoverishment of the rural population than the urban. There is no gender difference. Overall impoverishment added by tourism expenditure is about three percent. These findings suggest that drivers of domestic tourists' expenditure should not be underestimated by the policymakers in India while designing the policy for poverty reduction. Moreover, policymakers and researchers need to analyse the monthly spending behaviour of mid-aged people, Hindus and the rural population in India as they are more likely to be dragged into poverty due to their tourism spending.